Sex and Education: Does Sexual Debut During Adolescence Lead to Poor Grades?. Issue 2 (20th May 2019) - Whitworth, Tanya Rouleau; Paik, Anthony
Abstract : CONTEXT: Because many U.S. teenagers experience their first sexual intercourse during high school, understanding whether sexual behavior and academic performance are related is important. However, research on sexual debut and grades has produced inconsistent findings. METHODS: Data collected over four years from a specific cohort (1, 321 eighth‐ and ninth‐graders) of a nationally representative longitudinal study, the 1997 National Longitudinal Survey of Youth, were examined using fixed‐effects regression models to assess the relationship between first sexual intercourse and grade point average (GPA). RESULTS: Overall, no relationship was found between students' first sexual intercourse and GPA. For black females and Latinos of either gender, having had first sexual intercourse was associated with a lower GPA (coefficients, –216 and –161, respectively, corresponding to grade point decreases multiplied by 100). For black females, this association was observed only in the context of romantic relationships (–243). The predicted GPAs for black females aged 14 or 15 who reported first intercourse in a romantic relationship were significantly lower than those for their counterparts who had not had intercourse, whereas at 18 this was reversed. For Latinos, the predicted GPAs of 14‐ and 15‐year‐olds who had had sex were also lower than those of their sexually inexperienced counterparts. CONCLUSIONS: Although first sexual intercourse may not disrupt the academic performance of older adolescents, it may contribute to lower grades among younger minority adolescents. Further research is needed using such contextual variables as age, race, ethnicity, gender and relationship context.